Job Satisfaction Among Faculty in Standardized Residency Training Programs in Heilongjiang Province, China: A Cross-Sectional Study - Chen J; Li H; Xin Y; Wang H (Risk Management and Healthcare Policy)
Jiaxin Chen,1 Honglong Li,2 Yang Xin,3 Haijun Wang4 1School of Public Health, Qiqihar Medical University, Qiqihar, Heilongjiang, People’s Republic of China; 2School of Mental Health, Qiqihar Medical University, Qiqihar, Heilongjiang, People’s Republic of China; 3College of Chemistry and Chemical Engineering, Qiqihar University, Qiqihar, Heilongjiang, People’s Republic of China; 4School of General Medicine and Continuing Education, Qiqihar Medical University, Qiqihar, Heilongjiang, People’s Republic of ChinaCorrespondence: Haijun Wang, School of General Medicine and Continuing Education, Qiqihar Medical University, 333 Bukui Street, Jianhua District, Qiqihar, 161000, People’s Republic of China, Tel/Fax +86452-2663418, Email whj4830369@163.comPurpose: Job satisfaction among faculty in standardized residency training programs has been underexplored. The objective of this study is to investigate job satisfaction among these faculty members and identify associated determinants.Methods: An online cross-sectional survey was conducted with 4581 teachers in Heilongjiang Province from 18 to 30 May 2022, using a census method. The survey collected demographic information and assessed satisfaction using the Minnesota Satisfaction Questionnaire-Short Form. Predictors of job satisfaction were identified using multiple linear regression analysis in SPSS 24.0.Results: The survey achieved a 91.12% response rate (4174/4581). The average satisfaction score of the respondents teachers was 4.30± 0.70. The top three items with the highest satisfaction scores were “the chance to work alone on the job” (4.46± 0.68), “the way my job provides for steady employment” (4.45± 0.68), and “the freedom to use my own judgment” (4.43± 0.69). The lowest-scoring items “the chances for advancement on this job” (4.02± 1.03), “my pay and the amount of work I do” (4.08± 0.96), and “the praise I get for doing a good job” (4.10± 0.93). Multiple linear regression analysis revealed that geographical area, registered general subjects, age, administrative position, monthly income, daily working hours, and overtime frequency were significant factors influencing job satisfaction (P < 0.05).Conclusion: The level of job satisfaction among standardized residency training faculty in Heilongjiang Province was generally high. High satisfaction was associated with residing in economically developed areas, having registered general subjects, holding administrative positions, earning high income, working shorter few hours daily and having a low frequency of overtime.Keywords: medical education, job burnout, job satisfaction, standardized residency training